Vaginismus and Dyspareunia: A Comparative Review of Female Sexual Pain Disorders - Melike Çarıkçı; Ayhan Çakıcı (Clinical Journal of Health Sciences, 2026)
Vaginismus and dyspareunia are among the most prevalent female sexual pain disorders and have a substantial impact on sexual functioning, psychological well-being, and intimate relationships. Although these disorders were historically classified as separate diagnostic entities, they were unified under the diagnosis of Genito-Pelvic Pain/Penetration Disorder (GPPPD) in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5). Nevertheless, this diagnostic integration has generated ongoing debate regarding whether clinically meaningful differences between the two conditions remain sufficiently recognized. Vaginismus is primarily characterized by involuntary pelvic floor muscle contraction, intense fear, anxiety, and avoidance of vaginal penetration, whereas dyspareunia is characterized predominantly by superficial or deep genital pain during sexual intercourse and is more frequently associated with identifiable organic conditions. This review comparatively examines the diagnostic characteristics, clinical manifestations, etiological mechanisms, psychosocial consequences, and current treatment approaches associated with vaginismus and dyspareunia. Recent national and international studies were systematically reviewed, with particular attention given to the biological, psychological, relational, and sociocultural factors contributing to the development and maintenance of these disorders. The reviewed evidence indicates that vaginismus is predominantly associated with psychogenic mechanisms involving fear, anxiety, and avoidance, whereas dyspareunia is more commonly related to biological conditions, including infections, hormonal changes, pelvic disorders, and neurophysiological mechanisms. Nevertheless, findings consistently demonstrate that both disorders develop through complex interactions among biological, psychological, and sociocultural factors. In conclusion, despite their classification under a single diagnostic category in DSM-5, distinguishing the predominant clinical features of vaginismus and dyspareunia remains essential for accurate differential diagnosis, individualized treatment planning, and improved clinical outcomes.